2016
DOI: 10.1080/02786826.2016.1185509
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for quantifying the volatile mixing state of an aerosol

Abstract: Mixing state refers to the relative proportions of chemical species in an aerosol, and the way these species are combined; either as a population where each particle consists of a single species ('externally mixed') or where all particles individually consist of two or more species ('internally mixed') or the case where some particles are pure and some particles consist of multiple species. The mixing state affects optical and hygroscopic properties, and quantifying it is therefore important for studying an ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 43 publications
(48 reference statements)
1
35
0
Order By: Relevance
“…Note that this measurement is independent of the particle losses in the hot or cold stripper, as particle losses in the strippers do not affect the median mass of the distribution measured by CPMA because the particles going through the strippers have the same mobility (Dickau et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that this measurement is independent of the particle losses in the hot or cold stripper, as particle losses in the strippers do not affect the median mass of the distribution measured by CPMA because the particles going through the strippers have the same mobility (Dickau et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…All instruments used in this study are identical to those in Dickau et al (2016). Figure 1 shows the experimental setup used to measure the Gnome particle emissions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can refer to individual chemical species, as in the studies by Riemer and West [13], Healy et al [15], O'Brien et al [16], Giorio et al [24], and Fraund et al [25]. Alternatively, it can refer to species groups, as in Dickau et al [26] who quantified mixing state with respect to volatile and non-volatile components. Since we are concerned with CCN properties in this paper, we will group the chemical model species according to hygroscopicity, defining two species groups.…”
Section: Bulk Population (Gamma) Species Diversitymentioning
confidence: 99%
“…This methodology has been applied to a handful of laboratory and field studies, to date. In the laboratory, Dickau et al (2016) used aerosol sizing and mass instrumentation to quantify the volatile mixing state of soot. Single particle mass spectrometry data from field studies in London 25 (Giorio et al, 2015) and as part the MEGAPOLI campaign in Paris (Healy et al, 2014b) found mixing state was dependent both upon time of day and air mass origin.…”
Section: Introductionmentioning
confidence: 99%